How is the Performance of Education in Indonesia? - Milawati, Milawati; Fahrudin, Abdul Rozak (International Review of Management and Marketing, 2021)
This study aims to see the effectiveness of education performance in Indonesia which has been budgeted in the state budget (APBN) from 1996 to 2020. This effectiveness can be evaluated from the number of gross enrollment rates aged 15 years and over. The number of gross enrollment rates is affected by the government spending in education sector, national per capita income, and national literacy rate that is measured by the number of literacy. This study uses Auto Regression Distributed Level (ARDL) model to see the government's performance in education sector in the short term and long term. The finding of the study shows that in the short term, the government's expenditure for education sector and national literacy level supports the effectiveness of education performance. Meanwhile in the long term, literacy level supports the effectiveness of education performance. Keywords: gross enrollment rate, literacy rate, government spending, national per capita income JEL Classifications: I21, I22, I25 DOI: https://doi.org/10.32479/irmm.10655